The empty seashell witchcraft and doubt on an Indonesian island - Bubandt, Nils (Singapore NUS Press, 2015)
"Explores what it is like to live in a world where cannibal witches are undeniably real, yet too ephemeral and contradictory to be an object of belief. In a book based on more than three years of fieldwork between 1991 and 2011, Nils Bubandt argues that cannibal witches for people in the coastal, and predominantly Christian, community of Buli in the Indonesian province of North Maluku are both corporeally real and fundamentally unknowable."-- Provided by publisher.
Introduction : the shell of the nautilus -- Witchcraft, doubt, and aporia -- The origins of witchcraft and the doubts of tradition -- Hopes, conversion, and millennial politics -- Christianity and deception -- The viscerality of witchcraft and the corporeality of the world -- New Order modern -- Subjectivity, exchange, opacity -- Technology, money, and the futures of witchcraft.
"Copyright © 2014 by Cornell University"--Title page verso.
Includes bibliographical references (pages 263-284) and index.
Keywords: Witchcraft -- Indonesia -- Halmahera; Ethnology -- Indonesia -- Halmahera; Belief and doubt; Halmahera (Indonesia) -- Religion